Human impact on nature - Abduhalilov Abdumutal; Karimova Inobat; Khudayko'lova Madina; Muhammadov Tuygun (Zien Journals, 2022)
In this article, we can see the changes in natural landscapes as a result of the human’s attitude to nature, as well as the destruction of the future by mankind over the years.
Keywords: Milkov; “Tobiogen”; “Biogen”; Anthropogenic”; the newest era